Effect of Dietary Selenium on Protein and Lipid Oxidation and the Antioxidative Potential of Selected Chicken Culinary Parts during Frozen Storage - Małgorzata Korzeniowska; Bożena Króliczewska; Wiesław Kopeć (Journal of Chemistry)
The objective of the study was to evaluate the effects of inorganic and organic selenium in the diet of broiler chickens on the oxidative changes in the functional groups of proteins and total lipids, as well as the antioxidative potential of typical culinary parts fresh and frozen. Materials used in the nutrition study comprises one-day-old Flex broiler chickens randomly allocated to three dietary treatments: Control and SeN-fed diet enriched with 0.50 mg/kg of inorganic selenium (sodium selenite), and SeO-fed with diet containing 0.50 mg/kg of selenized yeast Yarrowia lipolytica. After slaughter, chicken carcasses were divided into the most typical culinary parts i.e., wings, outer and deep breasts, drumstick, thigh and back and analyzed in the fresh state and during frozen storage at −18°C until 90 days. The analyses undertaken during the study measured selenium concentration, CO, SH, and NH2 groups in the proteins, TBARS-expressing changes in the lipids, and antioxidative potential by ABTS, DPPH, and FRAP methods. The results of the study showed that the dietary selenium supplementation effectively increased the selenium concentration in all analyzed culinary parts of the chicken carcass, especially high in leg muscles. Selenium supplementation of the chicken diet significantly reduced the oxidative changes in the most important chemical reactive groups of the muscle myofibrillar proteins in all analyzed culinary parts. Both forms of selenium, organic and inorganic, were able to slow down the oxidation processes during first 30 days of the frozen storage of the meat. Longer storage could be only recommended for breast fillets, definitely not for the back part. The effect was much stronger in case of an organic selenium supplementation comparing to inorganic form of diet enrichment.